Active management of third stage of labour with special reference to misoprostol - Ahmed, Mariyam S.; Bhalerao, Anand N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Active management of third stage of labour is an effective method of preventing postpartum hemorrhage. It includes administration of uterotonic immediately after delivery of the baby, delaying cord clamping for at least 1-3 minutes to reduce rates of infant anaemia, performing controlled cord traction for removing the placenta and postpartum vigilance, ie, assess the uterine tone to ensure a contracted uterus; and continue to check every 15 minutes for 2 hours. If there is uterine atony, fundal massage should be performed and patient should be monitored more frequently. Though oxytocin is the best drug for routine prophylaxis, misoprostol is a relatively newer drug which is now included in the various guidelines for prevention and treatment of postpartum hemorrhage. It can be used as an effective and safe drug in areas with poor access to skilled healthcare providers and facilities.